Choosing homes, choosing schools - Lareau, Annette; Goyette, Kimberly A. (Russell Sage Foundation, 2014)
"A series of policy shifts over the past decade promises to change how Americans decide where to send their children to school. In theory, the expanded use of standardized test scores and the boom in charter schools will allow parents to evaluate their assigned neighborhood school, or move in search of a better option. But what kind of data do parents actually use while choosing schools? Are there differences among suburban and urban families? How do parents' choices influence school and residential segregation? What role ... [do] school concerns play in the preferences of white and minority parents for particular neighborhoods, and how [do] the racial and economic makeup of both neighborhoods and schools mutually reinforce each other? Choosing Homes, Choosing Schools adroitly addresses this gap and provides a firmer understanding of how Americans choose where to live and send their children to school."--Back cover